Potential role of tumor-infiltrating T-, B-lymphocytes, tumor-associated macrophages and IgA-secreting plasma cells in long-term survival in the rectal adenocarcinoma patients - Zinovkin, Dmitry A.; Kose, Suheyla Y.; Nadyrov, Eldar A.; Achinovich, Sergey L.; Los', Dmitry M.; Gavrilenko, Tatyana E.; Pranjol, Md Zahidul Islam (Pergamon-Elsevier Science Ltd, 2021)
Aims: Many studies investigated the associations between the role of immune cells of rectal cancer microenvironment and survival during the first 5 years post-surgery. This is problematic as this disease has the potential to progress even after 5 years after relapse and infiltrating immune cells could play key roles. Therefore, this retrospective study investigates expression and roles of tumor-infiltrating T-lymphocytes (TIL-T), tumorinfiltrating B-lymphocytes (TIL-B), IgA+ plasma cells (IgA+ PC) and tumor-associated macrophages (TAM) in patients with or without progression over 5 years survival with rectal adenocarcinoma. Main methods: Here we used immunohistochemical staining of CD3, CD20, IgA, CD68 positive cells and its detection in rectal cancer stroma. Data was analyzed using Mann Whitney U test, ROC, survival and Cox's regression analysis. Key findings: The number of TIL-T (p = 0.0276), TIL-B (p < 0.0001) and IgA+ PC (p = 0.015) immune cells was significantly higher in rectal cancer stroma of patients with favorable outcome. Univariate Cox's regression analysis revealed a predictive role of TIL-T (HR = 0.482; 95% CI, 0.303 to 0.704; p < 0.0001), TIL-B (HR = 0.301; 95% CI, 0.198 to 0.481; p < 0.0001) and IgA+-PC (HR = 0.488; 95% CI, 0.322 to 0.741; p < 0.0001). Multivariate Cox's regression analysis showed prognostic role of TIL-B (HR = 0.940; 95% CI, 0.914 to 0.968; p < 0.0001) and IgA+-PC (HR = 0.985; 95% CI, 0.975 to 0.996; p = 0.006) play role in long time survival. Significance: CD20+ TIL-B and IgA+ cells have significant associations with long -term survival of patients with rectal cancer, with potential therapeutic intervention in cancer immunotherapy.
Keywords: Rectal cancer; Tumor-infiltrating T-lymphocytes; Tumor-infiltrating B-lymphocytes; Tumor microenvironment; IgA(+) plasma cells